2019
DOI: 10.1089/jwh.2018.7515
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Coordinated Social Media Strategy to Improve Dissemination of Research and Collect Solutions Related to Workforce Gender Equity

Abstract: Background: To increase awareness, search for solutions, and drive change, disparity-related research needs to be strategically disseminated. This study aimed to quantify whether a social media strategy could: (1) amplify dissemination of gender equity-related articles and (2) collect proposed solutions to gender equity issues. Methods: In April 2018, eight published journal articles covering separate gender equity issues were presented in a 1-hour Twitter chat hosted by Physician's Weekly. Metrics data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 39 publications
0
31
0
1
Order By: Relevance
“…Studies have shown the role of Twitter, for example, in promoting women physician's needs and expanding dissemination of research by female scientists. 7 A study of a closed Facebook group for the Hematology/ Oncology Women Physician Group found that the platform was beneficial for both professional medical concerns and for social support. 8 From a feminist theory lens, social media platforms may serve as important tools to promote inclusiveness and respect.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the role of Twitter, for example, in promoting women physician's needs and expanding dissemination of research by female scientists. 7 A study of a closed Facebook group for the Hematology/ Oncology Women Physician Group found that the platform was beneficial for both professional medical concerns and for social support. 8 From a feminist theory lens, social media platforms may serve as important tools to promote inclusiveness and respect.…”
Section: Introductionmentioning
confidence: 99%
“…Impact studies have reported the use of social media interventions to promote original research articles published in academic journals in the subject areas of clinical pain sciences (ie, PLOS ONE ) [ 48 ], cardiology (ie, Circulation ) [ 46 , 47 ], radiology [ 52 ], emergency health [ 51 ] public health (ie, International Journal of Public Health ) [ 49 ], and women’s health (various journals) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 4 randomized controlled experiments, further referred to as RCTs [ 46 , 47 , 49 , 51 ], and 3 quasi-experimental trials [ 48 , 50 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…After an article is published, social media activity may increase the number of both downloads and eventual citations, particularly among those readily available to all readers, such as those with open access. 13,19,25,[30][31][32] Cawcutt et al 13 demonstrated that strategic social media dissemination of publications (via Twitter) can statistically increase the alternative metrics of a given article. A study that investigated the correlation between social media (specifically Twitter) and the conventional bibliometric of journal citations was published in the Journal of Medical Internet Research (JMIR).…”
Section: Alternative Metricsmentioning
confidence: 99%
“…10 The evolution of social media has created a new venue for rapid dissemination of information, advocacy on critical issues, and education to a broader audience. [11][12][13] Raising awareness of HAIs and AS research among healthcare providers, administrators, and even patients is the first step in improving the speed of change in clinical practice. 4 In this review, we discuss how social media platforms provide a conduit of implementation science for sharing research with broader audiences and how they may impact bibliometrics (statistical measures of the impact and reach of studies).…”
Section: Introductionmentioning
confidence: 99%